Evaluation of middle and deep geothermal resources reserves in Changqing Oilfield - GUO Lu,XIA Yan,DUAN Chenyang,GAO Wenbing,CHEN Kai,HOU Yayun,GUO Hong (Youqicang pingjia yu kaifa)
Geothermal energy, as a stable and sustainable clean energy source, is set to play a crucial role in China's energy structure transformation and the realization of the “double carbon” goal in the future. The Ordos Basin, noted for its abundant geothermal resources, still holds much untapped potential due to incomplete understanding of its reserves and distribution characteristics, and the relatively low level of exploration and development. Focusing on the Changqing Oilfield and its surrounding areas, the study delves into the geothermal geological characteristics using well data. It employs the unit volume method to estimate the geothermal resource reserves and conducts zoning based on the development and utilization potential of these resources. The study reveals that the formation structure in the area is relatively straightforward, with a general geothermal gradient of 2.2~3.0 ℃/hm. The primary thermal reservoir consists of conductive Mesozoic sandstone, while other thermal reservoirs, except for Luohe Formation, exhibit poor water yield. The geothermal resources in the region are distributed with higher concentrations in the western areas and lower in the east, with a total amount of 79.91 × 1017 kJ. Among this a recoverable capacity of 6.39 × 1017 kJ, and a geothermal fluid reserve of 2.47 × 1012 m3 have been identified Blocks such as Hongliugou-Dashuikeng-Jicun-Shancheng block, Zhanggoumen-Liuquzhen-Sanchazhen block and the block near Qingyang exhibit significant potential for geothermal resource development. Therefore, the study recommends prioritizing the redevelopment of abandoned oil and gas wells, alongside the construction of medium and deep casing heat exchange systems. This approach would facilitate the effective development and utilization of geothermal resources in these areas.